The interaction of an amorphous metal–organic cage-based solid (aMOC) with miRNA/DNA and its application on a quartz crystal microbalance (QCM) sensor. Issue 4 (12th December 2019) - Jin, Xia; Zhang, Yu-Ping; Li, Dian-Mei; Ma, Ding; Zheng, Sheng-Run; Wu, Chu-Hong; Li, Jia-Ying; Zhang, Wei-Guang
Abstract : The interaction between an aMOC and miRNA/DNA is studied and the use of the aMOC as an effective amplifier in a QCM sensor to detect miRNA is developed for the first time. Abstract : The interaction between an aMOC and miRNA/DNA is studied and the use of a signal probe DNA (spDNA)@aMOC complex as an effective amplifier in a QCM sensor to detect miRNA is developed. The signal can be significantly enhanced, which leads to improved performance when detecting and distinguishing miRNAs.